The Making of Solar Systems as a One Of Geography Learning Media in Sma N 2 Batang Anai, Padang Pariaman Regency and SMA N 5 Bukittinggi, Bukittinggi City - Chandra, Deded; Wilis, Ratna; Susetyo, Bigharta Bekti; Rahmi, Lailatur; Arief, Dian Adhetya; Wijayanto, Bayu; Prarikeslan, Widya; Marya, Sri; Nova, Sari; Ramadhan, Risky (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This article aimed to improve the ability of teachers and students to create the miniature media of the solar system and improve teachers` understanding and abilities in terms of understanding pedagogical aspects those could be seen from the process of designing a Learning Implementation Plan (RPP) especially in terms of choosing a model or learning method. This activity was held at SMAN 2 Batang Anai, Padang Pariaman Regency and SMA N 5 Bukittinggi, Bukittinggi City by using training methods, questions and answers, also practices. Participants involved were geography teachers and students representatived in each class with 25 people. The form of the activity was conducting training related to designing effective learning media and conducting training related to making miniature solar systems to geography teachers and students. The results of the training carried out at SMAN 2 Batang Anai in Padang Pariaman Regency and SMA N 5 Bukittinggi in Bukittinggi City were in the form of a miniature solar system and increased abilities possessed by teachers and students in making learning media in this case was a miniature solar system. From this training, teachers had increased the understanding / ability of pedagogical aspects which could be seen from the process of designing lesson plans, especially in the terms of choosing a learning model. Geography teachers also understood more about adequate competence in terms of designing and utilizing media so that quality and effective learning was created.